Sex and maturity modulate the link between sprint mechanics and multidirectional speed - Pedro Muñoz-Fole; Andrés Baena-Raya; Ezequiel Rey; Filipe Almeida Conceição; Manuel Avelino Giráldez-García; Alexis Padrón-Cabo (International Journal of Sports Medicine, 2026)
This study aimed to (I) evaluate the influence of maturity and sex on the horizontal force-velocity (F-V) profile and multidirectional speed performance in youth basketball players and (II) analyze the sex- and maturity-specific associations of the mechanical variables derived from the horizontal FV profile with curvilinear sprint (CS) and change of direction (COD) performance. Ninety-nine youth basketball players from an elite academy were classified into two maturational groups based on their estimated years from peak height velocity (PHV) (mid-PHV and post-PHV). A cross-sectional design was implemented to compare the mechanical variables of the F-V profile (theorical maximal force (F0) and velocity (V0), maximal power output (Pmax) and ratio of horizontal-to-resultant force (RFpeak) across maturation and between sexes. These variables were also analyzed in relation to CS and COD performance. Post-PHV group exhibited significantly greater horizontal FV profile parameters (ES from 0.70 to 2.06), and faster CS and COD performances (ES from 0.29 to 2.49), compared to mid-PHV group in both sexes. Additionally, V0, Pmax and RFpeak were moderately to largely associated (rrange from 0.41 to 0.81) with faster CS and COD performance in both mid- and post- PHV men players. These findings highlight the relevance of considering individual FV profiles to monitor performance and better understand multidirectional speed across maturation.